2003
DOI: 10.1080/00015458.2003.11679422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Ultrasonic Dissector in Thyroid Surgery. A Prospective Randomised Study

Abstract: Even if the use of the ultrasonic dissector is not of major interest in terms of patient management or cost-saving in the context of total thyroidectomy, essential advantages reside in significant reductions of operating time, blood loss and organ injury, (particularly parathyroid). The reduced operating time undoubtedly represents a positive feature of the ultrasonic dissection technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 0 publications
4
68
1
3
Order By: Relevance
“…Indeed, we found that robotic assistance was associated with significant differences in mean total SIS-6 scores and that a significantly lower percentage of patients reported swallowing discomfort at all postoperative time points, indicating that robot-assisted thyroidectomy can beneficially affect swallowing. This may be attributable to optical magnification of the operative field, to the precise handing possible using a flexible endoscopic instrument, and to a decrease in stress on the paraesophageal space with the use of the Harmonic scalpel [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that robotic assistance was associated with significant differences in mean total SIS-6 scores and that a significantly lower percentage of patients reported swallowing discomfort at all postoperative time points, indicating that robot-assisted thyroidectomy can beneficially affect swallowing. This may be attributable to optical magnification of the operative field, to the precise handing possible using a flexible endoscopic instrument, and to a decrease in stress on the paraesophageal space with the use of the Harmonic scalpel [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Clips work for large vessels and are subject to dislodgment, whereas staples are wasted and costly for multiple single-vessel applications. Lasers are hindered by the risk of injury to many vital structures (e.g., recurrent nerves) in the operative field, and bipolar electrocautery does not give the surgeon the freedom of applicability at different angles [5].…”
Section: Discussionmentioning
confidence: 99%
“…Tiroidektomide Harmonic Scalpel son yıllarda yaygın olarak kullanılmakta olup etkinliği ile ilgili bir çok çalışma yapılmıştır (3,4,6,7,(9)(10)(11)(12)(13)(14). Harmonic Scalpel'ın kolay kullanımı ve manipülasyonu, diseksiyon, kesme ve koagülas-yon işlemini aynı anda yapabilmesi nedeniyle operasyon süresini kısalttığı bildirilmiş ve bununda cihazın en önemli avantajı olduğu vurgulanmıştır (6,7,(15)(16)(17) (10,18,19,22).…”
Section: Discussionunclassified
“…Harmonic Scalpel'ın kolay kullanımı ve manipülasyonu, diseksiyon, kesme ve koagülas-yon işlemini aynı anda yapabilmesi nedeniyle operasyon süresini kısalttığı bildirilmiş ve bununda cihazın en önemli avantajı olduğu vurgulanmıştır (6,7,(15)(16)(17) (10,18,19,22). Çalışmamızda her iki grupta da kalıcı RLS hasarı gözlenmedi.…”
Section: Discussionunclassified